Mosaic dominant TUBB4A mutation in an inbred family with complicated hereditary spastic paraplegia. Issue 6 (15th March 2015) - Kancheva, Dahlia; Chamova, Teodora; Guergueltcheva, Velina; Mitev, Vanio; Azmanov, Dimitar N.; Kalaydjieva, Luba; Tournev, Ivailo; Jordanova, Albena
Abstract Background Mutations in TUBB4A have been associated with a spectrum of neurological conditions, ranging from the severe hypomyelination with atrophy of the basal ganglia and cerebellum syndrome to the clinically milder dystonia type 4. The presence of movement abnormalities was considered the common hallmark of these disorders. Methods Clinical, neurological, and neuroimaging examinations, followed by whole exome sequencing and mutation analysis, were performed in a highly consanguineous pedigree with five affected children. Results We identified a novel c.568C>T (p.H190Y) TUBB4A mutation that originated de novo in the asymptomatic mother. The affected subjects presented with an early‐onset, slowly progressive spastic paraparesis of the lower limbs, ataxia, and brain hypomyelination, in the absence of dystonia or rigidity. Conclusions Our study adds complicated hereditary spastic paraplegia to the clinical spectrum of TUBB4A‐associated neurological disorders. We establish genotype–phenotype correlations with mutations located in the same region in the tertiary structure of the protein. © 2015 International Parkinson and Movement Disorder Society